Results of a randomized, prospective clinical trial evaluating metronomic chemotherapy in nonmetastatic patients with high‐grade, operable osteosarcomas of the extremities: A report from the Latin American Group of Osteosarcoma Treatment. Issue 6 (7th November 2016) - Senerchia, Andreza A.; Macedo, Carla Renata; Ferman, Sima; Scopinaro, Marcelo; Cacciavillano, Walter; Boldrini, Erica; Lins de Moraes, Vera Lúcia; Rey, Guadalupe; de Oliveira, Claudia T.; Castillo, Luis; Almeida, Maria Tereza; Borsato, Maria Luisa; et al.
Abstract : BACKGROUND: Metronomic chemotherapy (MC) consists of the administration of a low dose of chemotherapy on a daily or weekly basis without a long break to achieve an antitumoral effect through an antiangiogenic effect or stimulation of the immune system. The potential effect of MC with continuous oral cyclophosphamide and methotrexate in patients with high‐grade operable osteosarcomas (OSTs) of the extremities was investigated. METHODS: Patients with high‐grade OSTs who were 30 years old or younger were eligible for registration at diagnosis. Eligibility for randomization included 1) nonmetastatic disease and 2) complete resection of the primary tumor. The study design included a backbone of 10 weeks of preoperative therapy with methotrexate, adriamycin, and platinum (MAP). After surgery, patients were randomized between 2 arms to complete 31 weeks of MAP or receive 73 weeks of MC after MAP. The primary endpoint was event‐free survival (EFS) from randomization. RESULTS: There were 422 nonmetastatic patients registered (May 2006 to July 2013) from 27 sites in 3 countries (Brazil, Argentina and Uruguay), and 296 were randomized to MAP plus MC (n = 139) or MAP alone (n = 157). At 5 years, the EFS cumulative proportions surviving in the MAP‐MC group and the MAP‐alone group were 61% (standard error [SE], 0.5%) and 64% (SE, 0.5%), respectively, and they were not statistically different (Wilcoxon [Gehan] statistic = 0.724; P =.395). The multivariate analysis showed that necrosis grades 1 and 2, tumor size, and amputation were associated with shorter EFS. CONCLUSIONS: According to the current follow‐up, EFS with MAP plus MC is not statistically superior to EFS with MAP alone in patients with high‐grade, resectable OSTs of the extremities. Cancer 2017;123:1003–10. © 2016 American Cancer Society . Abstract : Because preclinical models have shown that metronomic chemotherapy may be effective against chemotherapy‐resistant tumors, the potential effect of metronomic chemotherapy with continuous oral cyclophosphamide and methotrexate in patients with high‐grade operable osteosarcomas of the extremities has been investigated. The current event‐free survival results do not support the routine use of cyclophosphamide and methotrexate as metronomic agents after standard chemotherapy for osteosarcoma. However, these results should not preclude further investigation into the potential of maintenance for patients with osteosarcomas.